Monolithic Nanoporous Crystalline Aerogels. Issue 15 (12th June 2013) - Daniel, Christophe; Longo, Simona; Ricciardi, Rosa; Reverchon, Ernesto; Guerra, Gaetano
<x xml:space="preserve">Abstract</x> Monolithic aerogels can be obtained by drying physical gels formed by linear uncross‐linked polymers. Particularly relevant are aerogels, the cross‐linking knots of which are nanoporous crystalline, which beside disordered amorphous micropores (typical of all aerogels and shown by scanning electron microscopy) also present all identical crystalline nanopores. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>